TSL751 : Practices and reflections in TESL / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2020)
This course is divided into two parts. The first part will initially introduce the participants to the relevant theories in ELT which include the principles in ELT, language learning and teaching, course design, language assessment. Additionally, the conceptual basis of ELT such as the curriculum type and Communicative Language Teaching will be discussed. It later will lead the participants into the discussions on the various methodologies in teaching English as a second language. The second part of the course will direct the reflective practices in ELT. The participants will use what they have learnt from the first and second parts of the course in their reflective practices. They will be asked to reflect on teaching in general and on their own teaching, examining critical incidents in teaching, exploring frustrations and excitements in teaching and learning language, exploring their own beliefs and philosophies of teaching language, analyzing their roles as teachers, and examining learner roles. This will then be the catalyst for self-reflection, critical inquiry into practice, and thus form the basis of their planning and decision-making. This course is relevant for classroom practitioners, teacher trainers, and those who aspire to leadership and administrative positions. The mode of delivery will be the seminar, group discussions, and individual presentations. The instructor will assume a lot of independent reading, research and study on the part of the participants.